An exploratory investigation of apoptotic and autophagic responses in peripheral blood mononuclear cells following maximal aerobic exercise in obese individuals. (2nd January 2022) - Huang, Chun-Jung; Rodriguez, Alexandra L.; Visavadiya, Nishant P.; Fico, Brandon G.; Slusher, Aaron L.; Ferrandi, Peter J.; Whitehurst, Michael
Abstract: Autophagy is a critical molecular process in promoting cell survival against apoptosis. This study examined whether maximal aerobic exercise-mediated apoptosis in obesity might be underlying the involvement of autophagy in the peripheral blood mononuclear cells (PBMCs). Twelve healthy male subjects (6 obese and 6 normal-weight) were recruited to participate in a maximal graded exercise test on a treadmill. Obese subjects exhibited a significantly lower Bax, but a higher Bcl-2 protein level in conjunction with a reduced Bax/Bcl-2 AUCi compared to normal-weight subjects following exercise. Furthermore, a greater LC3-II/LC3-I ratio and LC3-II/LC3-I AUCi was observed in obese subjects compared to normal-weight subjects. LC3-II/LC3-I AUCi was also positively associated with obesity-associated parameters (BMI, waist/hip circumference, and fasting insulin level), but was negatively correlated with Bax/Bcl-2 AUCi. These findings demonstrate that maximal aerobic exercise differentially mediates the intrinsic apoptotic pathway and autophagic activity in human PBMCs isolated from obese compared to normal-weight individuals.